Faktor-Faktor yang Berhubungan dengan Infeksi Hepatitis B pada Ibu Hamil di Kota Denpasar Tahun 2024: Studi Kasus-Kontrol - Ni Kadek Desi Kartika Sari (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Hepatitis B infection during pregnancy remains a significant public health issue due to its maternal and neonatal complications. This study aimed to identify factors associated with Hepatitis B infection among pregnant women in Denpasar City. A case-control design was conducted from February to April 2024 in four randomly selected community health centers, involving 128 pregnant women (64 HBsAg-positive and 64 HBsAg-negative) chosen through multistage random sampling. Data were collected using questionnaires and health center records, and analyzed with bivariate tests and logistic regression. Bivariate analysis showed significant associations between education level, parity, water source, and abortion history with Hepatitis B infection. Multivariate analysis revealed that women with primary/secondary education had a 3.4-fold higher risk of infection (AOR = 3.398; 95% CI: 1.272–9.075), and those using well water had nearly a threefold higher risk (AOR = 2.979; 95% CI: 1.343–76.607). History of blood transfusion increased the risk threefold (AOR = 3.022; 95% CI: 1.180–7.724), while abortion history was the strongest predictor (AOR = 26.267; 95% CI: 2.868–240.601). In conclusion, low education, unsafe water sources, blood transfusion, and abortion were key risk factors. Strengthening maternal education and infection control in reproductive health services is essential.